2019
DOI: 10.1039/c9ra04789a
|View full text |Cite
|
Sign up to set email alerts
|

Activating peroxymonosulfate by halogenated and methylated quinones: performance and mechanism

Abstract: This work describes the efficiency and mechanism of peroxymonosulfate (PMS) activation by benzoquinone with different functional groups for sulfamethoxazole degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Generally, the formation of 1 O 2 from the activation of SO 5 2− by TCBQ might be kinetically feasible, which might provide some theoretical support for the removal of sulfamethoxazole by PMS in the presence of 2,6dichloro-1,4-benzoquinone and tetrafluoro-1,4-benzoquinon with 1 O 2 as the primary oxidizing specie. 35 These results are supported by Figures S19 and S20.…”
Section: Peroxomonosulfatesupporting
confidence: 69%
“…Generally, the formation of 1 O 2 from the activation of SO 5 2− by TCBQ might be kinetically feasible, which might provide some theoretical support for the removal of sulfamethoxazole by PMS in the presence of 2,6dichloro-1,4-benzoquinone and tetrafluoro-1,4-benzoquinon with 1 O 2 as the primary oxidizing specie. 35 These results are supported by Figures S19 and S20.…”
Section: Peroxomonosulfatesupporting
confidence: 69%
“…The formation of a dioxirane intermediate has been observed and proposed to play a key role in PMS oxidation processes. 18,25,26 Therefore, quinone-like and phenol-like structures have been proposed to have positive effects on the removal of organic contaminants through PMS activation. Quinone-like and phenol-like functional groups are important constituents in dissolved organic matter (DOM), which is ubiquitous in aquatic environments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The concentration of Na 2 S 2 O 8 and monoaromatics were 5 mM and 100 μg/L, respectively, and the total volume was 40 mL. Samples were withdrawn and quenched with Na 2 S 2 O 3 periodically before analysis (Huber et al, 2005 ; Zhou et al, 2015 ; Zhang et al, 2019 ). A preliminary study demonstrated that Na 2 S 2 O 3 did not react with typical organics (1,2-dichloroethane, bromobenzene, and 1,2,4-trichlorobenzene) and had no interference with the analysis of the organics.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, new activating methods which utilize naturally occurring materials such as metal ores and organics have attracted much attention (Lin et al, 2019 ; Wu et al, 2019 ; Zhang et al, 2020 ). Quinones and organic matters containing quinone-like groups are ubiquitous in natural environment (Siqueira et al, 1991 ; Cory and McKnight, 2005 ), and they have been found to be effective as the accelerator or activator in advanced oxidation process (Zhou et al, 2015 ; Zhang et al, 2019 ). For instance, quinones increased the oxidation rate of contaminants in Fenton-like system, which was ascribed to their role as an electron shuttle (Duesterberg and Waite, 2007 ).…”
Section: Introductionmentioning
confidence: 99%